Modulation of social behavior by the agouti pigmentation gene - Carola, Valeria; Perlas, Emerald; Zonfrillo, Francesca; Soini, Helena A.; Novotny, Milos V.; Gross, Cornelius T. (Frontiers in Behavioral Neuroscience, 2014)
Agouti is a secreted neuropeptide that acts as an endogenous antagonist of melanocortin receptors. Mice and rats lacking agouti (called non-agouti) have dark fur due to a disinhibition of melanocortin signaling and pigment deposition in the hair follicle. Non-agouti animals have also been reported to exhibit altered behavior, despite no evidence for the expression of agouti outside the skin. Here we confirm that non-agouti mice show altered social behavior and uncover expression of agouti in the preputial gland, a sebaceous organ in the urinary tract that secretes molecules involved in social behavior. Non-agouti mice had enlarged preputial glands and altered levels of putative preputial pheromones and surgical removal of the gland reversed the behavioral phenotype. These findings demonstrate the existence of an autologous, out-of-skin pathway for the modulation of social behavior.